Analysis of patient flow in the emergency department and the effect of an extensive reorganisation. Issue 2 (1st March 2003) - Miró, Ò; Sánchez, M; Espinosa, G; Coll-Vinent, B; Bragulat, E; Millá, J
Abstract : Objectives: To evaluate the different internal factors influencing patient flow, effectiveness, and overcrowding in the emergency department (ED), as well as the effects of ED reorganisation on these indicators. Methods: The study compared measurements at regular intervals of three hours of patient arrivals and patient flow between two comparable periods (from 10 February to 2 March) of 1999 and 2000. In between, a structural and staff reorganisation of ED was undertaken. The main reason for each patient remaining in ED was recorded and allocated to one of four groups: (1) factors related to ED itself ; (2) factors related to ED-hospital interrelation; (3) factors related to hospital itself; and (4) factors related to neither ED nor hospital. The study measured the number of patients waiting to be seen and the waiting time to be seen as effectiveness markers, as well as the percentage of time that ED was overcrowded, as judged by numerical and functional criteria. Results: Effectiveness of ED was closely related with some ED related and hospital related factors. After the reorganisation, patients who remained in ED because of hospital related or non-ED-non-hospital related factors decreased. ED reorganisation reduced the number of patients waiting to be seen from 5.8 to 2.5 (p<0.001) and waiting time from 87 to 24 minutes (p<0.001). Before the reorganisation, 31% and 48% of the time was considered to be overcrowded in numerical and functional terms respectively. After the reorganisation, these figures were reduced to 8% and 15% respectively (p<0.001 for both). Conclusions: ED effectiveness and overcrowding are not only determined by external pressure, but also by internal factors. Measurement of patient flow across ED has proved useful in detecting these factors and in being used to plan an ED reorganisation.